1996
DOI: 10.1007/s002640050065
|View full text |Cite
|
Sign up to set email alerts
|

Simplification of the Elmslie-Trillat procedure for patellofemoral malalignment

Abstract: We describe a modification of the Elmslie-Trillat operation which includes a lateral retinacular release and medial realignment of the tibial tuberosity, but omits medial capsulorraphy. Seventy-five patients were reviewed with a follow up longer than 2 years and the results compared with the conventional Elmslie-Trillat procedure, which consists of lateral release, medial realignment of the tuberosity and medial capsulorraphy. The simpler operation can work as well and the period of rehabilitation is shorter. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 10 publications
1
6
0
1
Order By: Relevance
“…Ten studies reported the incidence of symptomatic hardware removal, [12][13][14][15][16][17]19,20,23,25 7 studies made no mention of symptomatic hardware, [9][10][11]18,21,26,27 and all hardware was removed regardless of symptoms in …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ten studies reported the incidence of symptomatic hardware removal, [12][13][14][15][16][17]19,20,23,25 7 studies made no mention of symptomatic hardware, [9][10][11]18,21,26,27 and all hardware was removed regardless of symptoms in …”
Section: Resultsmentioning
confidence: 99%
“…There were 472 direct medialization procedures (ElmslieTrillat technique) in 11 studies, [10][11][12]14,15,17,19,[22][23][24]26 193 anteromedialization procedures (Fulkerson technique) in 5 studies, 9,13,20,25,27 and 102 procedures in 3 studies 16,18,21 in which the tibial tubercle was completely detached for medialization, distalization, or a combination.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The surgical technique of the modified ET procedure was performed as reported by Tomatsu et al 12 First, the condition of the cartilage and tracking of the patellofemoral joint were observed by arthroscopy. Arthroscopic treatment for cartilaginous injury was performed whenever possible.…”
Section: Surgical Techniquementioning
confidence: 99%